The role of focused assessment sonography for trauma (FAST) on the outcomes in patients with blunt abdominal trauma following non-operative therapy: A cohort study - Wahyuningtias, Dewi Sukorini; Fauzi, Aditya Rifqi; Purnomo, Eko; Sofi, Imam (Elsevier Ltd, 2022)
Background: The non-operative management of blunt abdominal trauma had a high success rate and is expected to reduce the length of hospitalization and patients' morbidity. Here, we aim to evaluate the outcomes of patients with blunt abdominal trauma after non-operative management and associate them with prognostic factors. Methods: We performed a retrospective analysis on patients with blunt abdominal trauma who received non-operative management (NOM) at our institution from April 2018 to April 2021. Results: Two hundred eleven patients were included in this study who underwent non-operative management. Most of the subjects (73) were males, with male to female ratio of 2.7:1. Most patients aged 20–29 years old (29.4), FAST negative (62.1), minor injured (45), successfully managed nonoperatively (98.6), received no transfusion (38.9), and injured due to traffic accident (80.1). ISS was significantly associated with FAST (p = 0.028), while male gender, NLR, PLR, and blood transfusion did not (p > 0.05). The presence of external injury was associated with FAST results (p = 0.039), while the head, facial, thoracic, pelvic, and skeletal injuries did not (p > 0.05). We also found a significant correlation between blood transfusion and patient survival with NOM outcomes (p = 0.047 and p = 0.041, respectively). Furthermore, external injury significantly correlated with NOM outcomes (p = 0.042). Multivariate analysis showed that external and pelvic injury was significantly associated with NOM outcomes (p < 0.0001 and p = 0.036, respectively). Conclusions: The results of the FAST examination were not associated with the outcome of non-operative therapy. Moreover, the successful outcome of NOM might be affected by blood transfusions, the presence of external injuries, and pelvic injury. © 2022